Extremely high maternal alkaline phosphatase serum concentration with syncytiotrophoblastic origin. Issue 1 (27th December 2004) - Boronkai, A; Than, N G; Magenheim, R; Bellyei, S; Szigeti, A; Deres, P; Hargitai, B; Sumegi, B; Papp, Z; Rigo, J
Abstract : An extremely high alkaline phosphatase (AP) concentration (3609 IU/litre) was found in a 20 year old primigravida at 37 week's gestation, prompting an examination of its histological and cellular origin. Immunohistochemistry and western blots using antibodies against AP, Ki-67, phospho-protein kinase B (Akt), phospho-p44/42 mitogen activated protein kinase/extracellular signal regulated kinase 1/2 (MAPK/Erk1/2), phospho-glycogen synthase kinase-3β (GSK-3β), phospho-stress activated protein kinase/c-Jun N-terminal kinase, total-Akt, total-GSK-3β, and phospho-p38-MAPK were carried out on index and control placental samples of the same gestational age. Compared with controls, staining of the index placenta showed minimal AP labelling of the brush border and remarkable positivity of the intervillous space. Cytotrophoblastic proliferation was 8–10% in the index placenta compared with 1–2% in controls. The index placenta also had raised concentrations of protein kinases with important roles in cell differentiation. The proliferation and differentiation rates of the cytotrophoblasts were found to be five times higher in index samples than in controls. It is hypothesised that loss of syncytial membranes in immature villi led to increased AP concentrations in the maternal circulation and decreased AP staining of the placenta. Loss of the syncytium might also stimulate increased proliferation of villous cytotrophoblasts, which would then fuse and maintain the syncytium.